Influence of Green Distribution on Performance of Private Oil and Gas Marketing Firms in Kenya: Moderating Influence of Government Regulations - Obiso , Evans I.; Maendo , Densford; Musau, Enock; Waribu , James (African Journal of Education,Science and Technology (AJEST), 2023)
Globally, the oil and gas industry account for the major environmental tragedies leading to creation of reliability issues from policy makers and trust concerns from the community. Kenya’s carbon dioxide and greenhouse gas emissions increased from 7.82 million tonnes to 16.15 million tonnes, recording the highest levels of carbon dioxide and greenhouse gases in the country in 2021. Kenya’s private oil and gas sector, churns out 60 million litres of waste oil annually but only 5% of the waste is handled and disposed of properly. The purpose of this research was to establish the influence of green distribution on performance of private oil and gas marketing firms in Kenya. Rationale of the study was to mitigate the adverse effects of private oil and gas activities on the environment through adoption of green distribution. The guiding theories included; the resource-based view and the natural resource-based view. The study was guided by the positivist philosophy. The research utilized a descriptive design. Target population was 1850 employees working for the 72 private oil and gas marketing firms in Kenya. The study used stratified random sampling that gave a representative sample. Primary information was gathered using a sample size of 470 employees, using self-constructed questionnaires which were dropped and collected after two weeks. A pilot test was conducted at National oil corporation of Kenya, using ten percent of the sample size. Validity was ensured by the experts’ review. Reliability of the tools was tested using Cronbach’s alpha value. An alpha value of 0.7 or above gave a suitable and satisfactory reliability. To test the strength of the relationship amongst variables, the Pearson’s product moment correlation was employed. Quantitative data was analyzed using both descriptive and inferential statistics. Simple linear regression analysis measured direct effects of variables. Hierarchical regression analysis tested the moderation effect of variables. Analyzed information was presented through statistical parameter estimates and tables. The study findings showed that green distribution had a positive and significant influence on firm performance (F=237.992, P<0.05). The results further showed a significant moderating effect of government regulation on the relationship between green distribution practices and firm performance. The study concluded that green distribution positively influenced performance of private oil and gas marketing firms in Kenya. The study recommended that private oil and gas marketing firms should adopt green distribution to improve their economic, environmental and social performance.